Basophils are dispensable for the recovery of gross locomotion after spinal cord hemisection injury. Issue 4 (17th November 2015) - Geurts, Nathalie; Vangansewinkel, Tim; Lemmens, Stefanie; Nelissen, Sofie; Geboes, Lies; Schwartz, Christian; Voehringer, David; Hendrix, Sven
Abstract : MCs are essential for functional repair after CNS trauma, where basophils do not affect gross locomotor recovery after SCI. Abstract : Basophils are the smallest population of granulocytes found in the circulation. They have crucial and nonredundant roles in allergic disorders, in protection from parasite infections, in autoimmunity, and in the regulation of type 2 immunity. They share phenotypic and functional properties with mast cells, which exert substantial protective effects after traumatic brain injury and spinal cord injury, although they are considered one of the most proinflammatory cell types in the body. In contrast, the in vivo functions of basophils in central nervous system trauma are still obscure and not well studied. In this study, we show that by comparing spinal cord injury in wild type vs. basophil‐deficient Mcpt8Cre transgenic mice, the locomotor recovery is not affected in mice depleted in basophils. In addition, no substantial differences were observed in the lesion size and in the astrocytic and macrophage/microglia reaction between both mouse strains. Hence, despite the multiple properties shared with mast cells, these data show, for the first time, to our knowledge, that basophils are dispensable for the functional recovery process after hemisection injury to the spinal cord in mice.